Perkembangan Penelitian Metode Deteksi Kandungan Babi untuk Menjamin Kehalalan Produk Pangan Olahan - Elisa Andriyani; Nor Lutfi Fais; Siti Muarifah (Journal of Islamic Studies and Humanities, 2019)
Halal food is the most important thing to be considered by the Indonesian Muslim community. Halal food must be free from pork contents both as a basic ingredient and in the manufacturing process. Halal issues arise when there is a process of mixing meat or lard (adulteration) in halal animal meat for economic purposes. This research is a literature study that aims to examine the development of research on methods of detection of pig content in food products to ensure a food product is free from pig content and its derivatives. The method used is the study of literature in the form of journal articles, proceedings, conferences, online news and official sites that have relationships or keywords related to the method of pig content detection. The assessment results show that the detection methods that can be used are PDK (Pork Detection Kit) and enzyme-linked immunosorbent assay (ELISA) analysis methods to detect pig protein. RT-PCR (Real-Time Polymerase Chain Reaction) and digital PCR duplex droplet methods for detecting pig DNA. Gas chromatography (GC) methods, UV-Vis spectroscopy and Fourier-transform infrared spectroscopy (FTIR spectroscopy) for analysis of lard. The digital PCR (dddPCR) duplex droplet method has a very specific ability to detect pork content in processed food products compared to other methods. The dddPCR detection and quantification system is suitable for quality control and routine analysis of meat products. This can be taken into consideration for the development of research methods to detect pork content in processed food products that are more effective and efficient in the future.